Women in Latin American : an anthology from Latin American perspectives. (Riverside, California : Latin American Perspectiv, 1979)
The marxist approach to the study of women and class struggle women, development, and anthropological facts and fictions--Economics, politics, and ideology: concrete studies on women in Latin America--The practice of the women's struggle.
Keywords: AMERICA LATINA; MUJERES EN DESARROLLO NACIONAL; CONDICION SOCIAL; MUJERES